2010
DOI: 10.1002/dvg.20607
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish gene knockdowns imply roles for human YWHAG in infantile spasms and cardiomegaly

Abstract: Summary: Williams-Beuren syndrome (WBS) is a neurodevelopmental disorder presenting with an elfin-like face, supravalvular aortic stenosis, a specific cognitivebehavioral profile, and infantile hypercalcemia. We encountered two WBS patients presenting with infantile spasms, which is extremely rare in WBS. Array comparative genomic hybridization (aCGH) and fluorescent in situ hybridization (FISH) analyses revealed atypical 5.7-Mb and 4.1-Mb deletions at 7q11.23 in the two patients, including the WBS critical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…44 Interestingly, zebrafish knocked down for YWHAG have reduced brain size and an increased diameter of the heart tube. 45 …”
Section: Discussionmentioning
confidence: 99%
“…44 Interestingly, zebrafish knocked down for YWHAG have reduced brain size and an increased diameter of the heart tube. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on ywhag1 knockdown phenotype and expression pattern, the hemizigosity of YWHAG has been proposed to contribute to epilepsy and cardiomegaly. 14 In a recent study, Ramocki et al 10 reported individuals with heterozygous microdeletions distally adjacent to the WBS region inclusive of HIP1, but not YWHAG in patients with variable expression and/or incomplete penetrance of epilepsy, learning difficulties, intellectual disabilities, and/or neurobehavioral abnormalities, suggesting that deletion of HIP1 is sufficient to cause neurological disease. Together with these collective findings, our results led to the postulation that HIP1 and YWHAG genes might contribute to the WBS neurological dysfunction when deleted along with other WBS genes.…”
Section: Patient Wbs166mentioning
confidence: 99%
“…The biological mechanism(s) of ISS in these syndromes are not known, except for Miller-Dieker syndrome in which the deletion of PAFAH1B1/LIS1 causes both abnormal primary glutamatergic and GABAergic interneuron migration [89, 96, 97]. Similarly, deletion of MAGI2 at 7q11.2 may be associated with ISS in Williams syndrome [16], although there are also reports of ISS in Williams syndrome patients with deletions that do not include MAGI2 [25, 98, 99]. Overall this suggests that copy number changes in key genes, in the right developmental context, influence the occurrence of ISS in these disorders.…”
Section: Iss With Predisposing Genotype Knownmentioning
confidence: 99%